Sources and Effects of Credit Accessibility on Smallholder Paddy Farms Performance: An Empirical Analysis of Government Subsidized Credit Program in Indonesia - Harianto, Harianto; Hutagaol, M. Parulian; Widhiyanto, Iman (International Journal of Economics and Financial Issues, 2019)
As part of strengthening food security and increasing farmers’ income, the government established a program to improve farmers’ access to working capital. However, the absorption of subsidized credits is still much lower than the allocation of credits provided by the government. This study aims to analyze the factors that are likely to affect farmers’ opportunities to access subsidized credit, and how the impact of access to credit affects the performance of paddy farming. The propensity score matching (PSM) method is employed in this research. The data in this study is from a farm household level survey. The results of the study showed that collateral, interest rate, farmer access experience to credit, farmer group quality, and financial literacy level have a significant effect on farmer accessibility to subsidized credit. Farmers’ access to subsidized credit significantly not only improved the productivity and profitability of paddy farming in the research area but household non-farm income as well. Keywords: credit accessibility, working capital, inputs allocation, productivity JEL Classifications: D240, G210, H25 DOI: https://doi.org/10.32479/ijefi.8388